Evaluation of Water Harvesting Dams using a Designed Score Card System - S.K. Dhar,; S.S. Grewal,; Goran Jonsson, (Journal of Soil and Water Conservation, 2022)
The Haryana Community Forestry Project supported by the European Commission plans to construct 18 water-harvesting dams (WHO)in the Shivalik  region in active collaboration with rural communities. The funding agency asked for the evaluation of first two dams to consider giving further funding support for the remaining dams. Appropriate evaluation criteria for WHDs were, however, lacking in spite of large-scale replication of the technology. Adopting, a scorecard system, the evaluation of first two WHDs constructed during 2001-02 at villages Bharauli of Panchkula district and Ibrahimpur of Yamuna Nagar district was, therefore, carried out. Out of the total score of 100 marks, 40 were allocated to technical evaluation, 10 marks- each for environmental impact and economic viability, 35 for evaluation of the participatory process and 5 marks for institutional linkages. Each set of criteria was sub-divided into smaller components and carefully assessed in consultation with project staff, beneficiaries and project records.Total cost of the WHDs including all components was Rs. 3.12 million in Bharauli and Rs. 0.88 million in Ibrahimpur with corresponding catchment of 90 and 30 hectares, storage capacity of 22.45 and 11.87 hectare metres, dam height of 14 and meters and cost per cubic meter of water stored as Rs. 13.91 and Rs. 7.41, respectively. Pre-\WHD wheat crop yield increased from 7.68 to 18.95 and 26.85 q/ha with one and two irrigations at Bharauli and from9.75 to 14.30 and 17.80 q/ha, at  Ibrahimpur, giving B:C ratios of 2.11 and 1.93 and IRR of 41.95 and64.1 per cent at Bharauli and Ibrahimpur, respectively. Bharauli village resource management committee (VRMC) could mobilize a social fund of Rs. 55,654 against Rs. 1300 by VRMC of Ibrahimpur. The VRMC at Bharauli held a large number of meetings to sort out issues, operationalised the water distribution system and hence showed a good maturity as compared to VRMC of Ibrahimpur. The water-harvesting project at Bharauli scored 77.44 marks and was labeled as green and the one at Ibrahimpur scored 57.2 marks and labeled as yellow. Giving due weight age to all natural and human factors, the study brought out that both the WHD are technically sound, socially acceptable, and economically viable with good rate of economic returns. The study recommended construction of the remaining WHDs wherever site conditions permit by active community participation and taking measures against siltation.